let-7e downregulation characterizes early phase colonic adenoma in APCMin/+ mice and human FAP subjects. - Annalisa Contursi; Maria Arconzo; Marica Cariello; Marilidia Piglionica; Simona D'Amore; Michele Vacca; Giusi Graziano; Raffaella Maria Gadaleta; Rosa Valanzano; Renato Mariani-Costantini; Gaetano Villani; Antonio Moschetta; et al. (PLoS ONE, 2021)
The crypt-villus axis represents the essential unit of the small intestine, which integrity and functions are fundamental to assure tissue and whole-body homeostasis. Disruption of pathways regulating the fine balance between proliferation and differentiation results in diseases development. Nowadays, it is well established that microRNAs (miRNAs) play a crucial role in the homeostasis maintenance and perturbation of their levels may promote tumor development. Here, by using microarray technology, we analysed the miRNAs differentially expressed between the crypt and the villus in mice ileum. The emerged miRNAs were further validated by Real Time qPCR in mouse model (ApcMin/+), human cell lines and human tissue samples (FAP) of colorectal cancer (CRC). Our results indicated that miRNAs more expressed in the villi compartment are negatively regulated in tumor specimens, thus suggesting a close association between these microRNAs and the differentiation process. Particularly, from our analysis let-7e appeared to be a promising target for possible future therapies and a valuable marker for tumor staging, being upregulated in differentiated cells and downregulated in early-stage colonic adenoma samples.